A field experiment on the use of biogeotextiles for the conservation of sand-dunes of the Baltic coast in Lithuania - Jankauskas, Benediktas; Jankauskiene, Genovaite; FullenMichael A (Hungarian Geographical Bulletin, 2012)
Extreme damage was caused by wave and wind erosion on sand dunes on the Baltic coast near Palanga in Lithuania. Waves breached a wide ‘corridor’ or ‘blowout’ through the coastal sand dune. A progressively widening breached blowout developed. There was a need to protect boundaries (walls) of the blowout from deflation and to encourage sand-dune accretion. The field experiment was performed to establish vegetation on the ‘walls’ and base of the blowout to stabilize the feature and stimulate sand-dune accretion. The hypothesis was tested that biogeotextiles could act as complementary measures for possible re-vegetation and temporary prevention of deflation. The application of biogeotextile mats, constructed from the palm-leaves of Borassus aethiopum (Borassus) and Mauritia fl exuosa (Buriti), has been investigated in field experiments on coastal sand dunes. Biogeotextiles effectively stored soil moisture during dry summer periods. Covering sand-dune slopes with biogeotextiles and planting local species of grasses, shrubs and trees enabled the stabilization of a breached ‘corridor’ through the sand-dune and a mean sand-dune accretion rate of 24.7 cm per year, over three years. The results of investigations show biogeotextile cover enabled stabilization and restoration of vulnerable ecosystems on the Baltic coastal sand-dune. Geotextile cover prevented further deflation of the blowout; biogeotextile cover increased moisture storage and encouraged vegetation growth (planted shrubs and grasses); and biogeotextiles improved microclimatic and moisture conditions for the development of planted sprouts of plants communities. In turn, these changes encouraged rapid sand accretion and ‘growth’ of the basal sand dune. These processes contributed to the restoration of the breached sand-dune, sand accumulation and improved ecosystem functioning.